1986
DOI: 10.1111/j.1471-6402.1986.tb00766.x
|View full text |Cite
|
Sign up to set email alerts
|

Race and Sex Differences In Sex Role Attitudes of Southern College Students

Abstract: A sample of southern college students is used to investigate race and sex differences among nine Likert‐type sex role attitudes. Results show that black and white men share a similar sex role orientation while black and white women also share a similar world view. There were only two instances where blacks were notably different from whites. First, blacks were more likely to feel that a woman's real fulfillment in life comes from motherhood, and second, blacks were more likely to feel that it was appropriate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Also for self-image, there was a Sex by Race by Pknow effect-black females scored higher than white females in both Pknow conditions, but for males who know scientists, blacks scored higher than whites, while for males who do not know scientists, whites scored higher than blacks. This result would suggest that black females are less bound by traditional sex roles than their white counterparts-a suggestion that has appeared before (see, e.g., Lyson, 1986). Finally, there was a two-way interaction of Race by Location in that rural blacks scored higher on self-image than urban blacks, while urban whites outscored rural whites.…”
Section: Resultsmentioning
confidence: 62%
“…Also for self-image, there was a Sex by Race by Pknow effect-black females scored higher than white females in both Pknow conditions, but for males who know scientists, blacks scored higher than whites, while for males who do not know scientists, whites scored higher than blacks. This result would suggest that black females are less bound by traditional sex roles than their white counterparts-a suggestion that has appeared before (see, e.g., Lyson, 1986). Finally, there was a two-way interaction of Race by Location in that rural blacks scored higher on self-image than urban blacks, while urban whites outscored rural whites.…”
Section: Resultsmentioning
confidence: 62%
“…In terms of probability samples, this claim has generally been made regarding African-American men only (Blee & Tickamyer 1995, Ransford & Miller 1983, Rice & Coats 1995. A similar claim is echoed in some convenience samples studies of women (Gackenbach 1978, Gump 1975 or both men and women (Lyson 1986). Ransford & Miller's (1983) work has been particularly often cited in terms of this pattern among men.…”
Section: Attitudes Toward Gender Rolesmentioning
confidence: 72%
“…On the other hand, where racial differences do appear in African American/white comparisons of role-related attitudes, they often follow an intriguing pattern. Whites are more critical of maternal employment than African Americans, seeing paid employment as less compatible with the role of wife/mother and as more harmful to children, both in probability samples (Bielby & Bielby 1984, Blee & Tickamyer 1986, Blee & Tickamyer 1995, Cazenave 1983a, Dugger 1988, Rice & Coats 1995 and in college student samples (Crovitz & Steinmann 1980, Lyson 1986, Murrell et al 1991. In addition, in studies relying on indices that combine a variety of gender-role attitude items that refer to both home and employment, African Americans are sometimes more egalitarian than whites, as is indicated in several studies that include probability samples of women (Fulenwider 1980, Harris & Firestone 1998, Mason & Bumpass 1975.…”
Section: Attitudes Toward Gender Rolesmentioning
confidence: 97%
“…Nevertheless, as men's and women's roles continue to diversify, it would be interesting to explore the relational needs of men with a similar methodology. In a similar way, the relational needs of women of color warrant further exploration, because research has suggested that the value placed on family by ethnic minorities may be in conflict with social conditions that favor work opportunities for minority women over minority men (Lyson, 1986). Finally, research must go beyond the macrovariables and look at the day-to-day social interactions of students to more fully understand their decision-making process regarding college and career.…”
Section: Discussionmentioning
confidence: 97%